Misogyny against climate justice activists - van der Heyden, Katrien (Kvinder, Køn & Forskning, 2024)
The 2019 climate strikes were led by women with Great Thunberg being the first to start the Fridays for Future schoolstrikes. Anuna followed this example in Belgium. Being in this leading position, both received a huge amount of online harassment. The harassers were mainly young boys. The harassment was mainly sexual. This goes to show how the patriarchal masculinity experienced by the boys is felt to be threatened and needs to be defended by instigating violence against women. The deconstruction of patriarchal masculinity into caring types of masculinities/humanities, is to be prioritised in feminist and climate movements.